Equal Health Opportunity for Unskilled Migrant Workers within Limited National Healthcare Scheme in Thailand's Context - Wanwadee Poonpoksin (Asian Social Work Journal, 2018)
Health is an important indicator of the population in every country, including migrant workers in destination countries, according to the provisions of international laws that govern health services without regard to the legal status of migrants. This article reviewed information from academic papers, research, and interviews with relevant personnel. The objective of this article is to point out information on health systems for migrants from the perspectives of both outsiders and insiders, which include research and data from interviews with the relevant health personnel in Thailand. The study indicated that academic papers published by foreigners see the Thai healthcare system as having a variety of problems in the exploitation of migrant workers, while Thai health personnel provides services without discrimination in all groups. In reality, Thai laws and national healthcare scheme require certain specific limited conditions for migrant workers for reasons of security, disease prevention, and control, including Thailand’s struggle to deal with an influx of both legal and illegal workers into the country. Therefore, it is not easy to manage the healthcare scheme in order to increase coverage and equality for migrants and Thais alike. This study attempts to understand the development direction of the Thai health system as it moves into the future to provide coverage for all involved parties based on social capital and feasibility of action under the health policies of the developing country destination of Thailand.